Study on the Performance Style and Improvisational Methods of the Dangdut Flute in the Original Genre Section Band - Ayu Soraya; Ibnu Amar muchsin (CV Edukastra Mandiri, 2025)
This research explores the performance style and improvisational methods of the dangdut flute in the Original Genre Section Band, focusing on their live interpretation of Cinta Rahasia. The flute, played by Bambang Kusmanto, serves not only as an accompaniment but also as a central expressive medium that enhances the lyrical and emotional character of the performance. Its role highlights the significance of the flute in shaping dangdut’s musical identity through both stylistic techniques and spontaneous improvisation. The study applies a qualitative descriptive method, with data collected through observation, semi-structured interviews, and performance documentation. Analytical procedures include performance analysis of musical techniques such as articulation, dynamics, and ornamentation, as well as thematic coding of improvisational practices and ensemble interactions. Results show that the flute’s performance style is marked by staccato, legato, vibrato, glissando, tremolo, and altissimo techniques, supported by posture, embouchure, and controlled breathing. Improvisation combines chordal and modal approaches, licks, rhythmic flexibility, and ornamental devices. The findings affirm that the flute embodies technical mastery, cultural symbolism, and dialogical interaction, making it a defining element of dangdut performance.